Managemen Keuangan Keluarga Pascaperceraian - Efrita Norman; Ermi Suryani (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
The family that is sakinah mawaddah warahmah is the dream and hope of everyone. Samawa households have extraordinary strength and become the backbone of the economic, family and community economic improvement. So, divorce is often the beginning of a family disaster. How can families get post-divorce survival? Clearly requires extraordinary financial management. This paper seeks to explore the issue of post-divorce family financial management. The results show that divorce is not the end of family life. With good financial management, many families are able to survive and even rise from a sense of adversity. Not infrequently the tempest even spurred families to be more diligent in doing productive activities. The results of the study concluded, family financial management was even able to resolve economic inequalities in the household, so as to reduce the increase in divorce rates. Especially when the level of science and tenacity of housewives is high. The higher the knowledge of housewives about management of family finances, the higher the economic survival rate of their families.